Tindakan Sosial Pemuka Agama Islam Terhadap Keberadaan Transgender - Notarous, Syahbudi (Tasamuh: Jurnal Studi Islam, 2020)
Abstract: The phenomenon of transgender in society leads to bring some reactions as well as the cases that need to be handled attentively. This research focuses on the thought and the social actions of Islamic leaders toward the existence of transgender. In conducting this research, the researcher used a social actions theory proposed by Max Weber and applied Snowball technique to decide the informant by using key informant. Qualitative description method is used as the main tool and Surabaya, East Java is selected as the location to gain the data. The data was obtained by in-depth interviews then it was analyzed inductively. The result of this research showed that all the informants have similar thoughts about transgender. The transgender is known as people who have a biological abnormalities which is indicated by having two genitals. The existence of the transgender is usually caused by an external factor such as the influence of the social environment. In this research, the researcher acquired several varieties of data which relate to the motivation of the Islamic religious leaders giving treatment to the transgender. The first informant tends to be motivated by traditional actions, the second informant tends to be motivated by affective actions, the third informant tends to be motivated by the rationality of values while the fourth and fifth informants tend to be motivated by the rationality of instrumental actions. Keyword: Social actions, Religious leaders of Islam, Transgender Abstrak Fenomena waria di masyarakat menimbulkan berbagai reaksi serta kasus yang perlu ditangani dengan serius. Penelitian ini berfokus pada pemikiran dan tindakan sosial para pemuka agama Islam terhadap eksistensi waria. Dalam melakukan penelitian ini, peneliti menggunakan teori tindakan sosial yang dikemukakan oleh Max Weber dan menerapkan teknik Snowball untuk menentukan informan dengan menggunakan informan kunci. Metode deskripsi kualitatif digunakan sebagai alat utama dan Surabaya, Jawa Timur dipilih sebagai lokasi untuk mendapatkan data. Data diperoleh dengan wawancara mendalam kemudian dianalisis secara induktif. Hasil penelitian menunjukkan bahwa semua informan memiliki kesamaan pemikiran tentang waria. Waria dikenal sebagai orang yang memiliki kelainan biologis yang ditandai dengan kepemilikan dua alat kelamin. Keberadaan waria biasanya disebabkan oleh faktor eksternal seperti pengaruh lingkungan sosial. Dalam penelitian ini, peneliti memperoleh berbagai macam data yang berhubungan dengan motivasi ulama dalam memperlakukan waria. Informan pertama cenderung termotivasi oleh tindakan tradisional, informan kedua cenderung termotivasi oleh tindakan afektif, informan ketiga cenderung termotivasi oleh rasionalitas nilai sedangkan informan keempat dan kelima cenderung termotivasi oleh rasionalitas tindakan instrumental. Kata Kunci: Aksi Sosial, Pemuka agam Islam, Waria/Transgender